2013
DOI: 10.1016/j.ajic.2011.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Behind the mask: Determinants of nurse's adherence to facial protective equipment

Abstract: Whereas increasing knowledge should enhance competence, strategies to improve adherence to recommended use of FPE in a busy and complex health care setting should focus on ready availability of equipment, training and fit testing, organizational support for worker health and safety, and good communication practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
3
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 32 publications
4
78
3
6
Order By: Relevance
“…It is important for hospital infection prevention programs to recognize that if face protection supplies are not available at every bedspace or room, a substantial proportion of providers may choose to omit using face protection in situations in which it is indicated. 4,5 In addition, our survey revealed that face protection was perceived by many providers as unnecessary, despite our inclusion of education about standard precautions as part of our hospital's required annual computer-based training for all clinicians.…”
Section: Discussionmentioning
confidence: 94%
“…It is important for hospital infection prevention programs to recognize that if face protection supplies are not available at every bedspace or room, a substantial proportion of providers may choose to omit using face protection in situations in which it is indicated. 4,5 In addition, our survey revealed that face protection was perceived by many providers as unnecessary, despite our inclusion of education about standard precautions as part of our hospital's required annual computer-based training for all clinicians.…”
Section: Discussionmentioning
confidence: 94%
“…One recent study found that nurses who were knowledgeable about respiratory protection recommendations were 2.9 times more likely to demonstrate competency in using an N95 FFR. 24 Both insufficient protection and improper use can negatively impact HCWs’ safety and health. The Jaeger et al study 10 involving the 2009 H1N1 pandemic found that increased rates of health care–associated transmission among HCWs were correlated with irregular use of proper PPE.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended that HCWs should wear N95 respirator masks when taking care of patients with TB or those surmised to have TB [21]. However, adherence to the use of facial N95 respirator masks is not always observed in clinical practice because of their inadequate availability [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Administrative infection control (IC) measures, such as educational programs, can reduce TB infection [7]. In addition, environmental control and personal protective equipment are crucial contributors to the prevention of TB transmission [1, 8]. The compliance of HCWs with IC measures is influenced by organizational, environmental, and individual factors.…”
Section: Introductionmentioning
confidence: 99%